1990
DOI: 10.1111/j.1467-8624.1990.tb02775.x
|View full text |Cite
|
Sign up to set email alerts
|

Concept Availability in the Causal Inferences of Children and Adults

Abstract: What supplies the concepts in causal inferences in story comprehension? This question was examined in 5 experiments. Elementary school children and college students listened to stories containing a "premise" sentence describing a character's intent in initiating a series of actions, followed by an unexpected "outcome." After each story, the subjects were asked inference questions about the reason for the outcome (Experiments 1-4) or asked to explain the outcome (Experiment 5). In the various experiments, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 29 publications
5
22
0
3
Order By: Relevance
“…The relation between knowledge accessibility and elaborative inferencing generally becomes more pronounced with increasing age; in young children, this relationship is somewhat unclear, possibly because they make relatively few elaborative inferences. The accessibility of semantic information, then, seems as important for knowledge-based inferencing as it is for text-based inferencing (Ackerman et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The relation between knowledge accessibility and elaborative inferencing generally becomes more pronounced with increasing age; in young children, this relationship is somewhat unclear, possibly because they make relatively few elaborative inferences. The accessibility of semantic information, then, seems as important for knowledge-based inferencing as it is for text-based inferencing (Ackerman et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…One of the language abilities most strongly related to comprehension at all ages is the size of a person's lexicon (Florit et al., , ; Nation & Snowling, ; Protopapas, Sideridis, Mouzaki, & Simos, ; Verhoeven & van Leeuwe, ). This is in part explained by vocabulary being, among other things, an indicator of world knowledge (Stahl, ; Stahl & Fairbanks, ), which is in turn essential for making inferences (Ackerman, Silver, & Glickman, ; Cain et al., ; Calvo, ). For example, in the text “The paleontologist packed the vertebra to take to his workplace,” the inference that the paleontologist was in an outdoor location, such as a mountain, requires knowing the word paleontologist , but it mostly requires knowledge about the field of paleontology, such as knowing the kinds of activities, people, elements, and places usually involved in it.…”
Section: Vocabulary: Breadth and Depthmentioning
confidence: 99%
“…Cain and Oakhill () found children with comprehension difficulties to be poor at inference‐making, and further research has shown that the relation between comprehension ability and inference‐making skill remains strong when knowledge base is controlled for (Cain, Oakhill, Barnes, & Bryant, ). However, an inference cannot be made without the ability to relate the information in the text to wider knowledge (Ackerman, Silver, & Glickman, ). Much experience is required to develop these thinking skills and instruction that promotes critical thinking, and considering alternatives in decision‐making has been shown to augment reading comprehension (Fletcher, Lyon, Fuchs, & Barnes, ).…”
Section: Introductionmentioning
confidence: 99%